Break Event Point (BEP) Analysis in Determining Service Prices at Duta Laundry Business: Analisis Titik Impas (BEP) dalam Penetapan Harga Layanan di Usaha Laundry Duta - Raisyah Arta Novia; Juliana Nasution; Yenni Samri Juliati Nasution (Academia Open, 2025)
General Background: The rapid growth of laundry services in urban Indonesia reflects increasing consumer demand for convenience, yet many micro-enterprises lack structured financial planning. Specific Background: Duta Laundry, a micro-scale service provider, sets prices based on market observation without applying analytical tools such as Break Even Point (BEP) analysis. Knowledge Gap: Prior studies on BEP in laundry businesses often overlook integration with daily service volume, month-to-month performance, and strategic pricing implications. Aims: This study analyzes the application of BEP to determine service price feasibility, evaluate sustainability, and provide strategic recommendations for micro-enterprises. Results: Findings indicate Duta Laundry’s BEP is reached at 107 transactions (749 kg) or Rp2,675,000 revenue per month, far below the realized 600 transactions (4,200 kg), indicating profitability. Comparative analysis shows May incurred a Rp710,000 loss due to high variable costs, while June achieved a Rp3,710,000 profit after cost efficiency improvements. Novelty: The study integrates BEP calculation with actual operational data, monthly performance comparison, and direct linkage to pricing and efficiency strategies. Implications: Implementing BEP in micro-service enterprises enhances data-driven decision-making, improves cost control, and supports sustainable competitiveness in volatile markets.Highlight : Determine the minimum service volume to avoid losses. Cost efficiency affects profits and business continuity. Data-based pricing increases competitiveness. Keywords : Break Even Point, Duta Laundry, Service Price, Cost Efficiency, Business Sustainability